Pharmacists’ Knowledge of Abnormal Uterine Bleeding in Women on Anticoagulant Therapy: A French Survey - Sibylle Frerebeau PharmD; Benjamin Planquette MD, PhD; Gabrielle Sarlon MD, PhD; Nicolas Gendron PharmD, PhD (Clinical and Applied Thrombosis/Hemostasis)
Objectives This study aimed to assess the role of community pharmacists in managing abnormal uterine bleeding (AUB) in women on anticoagulant therapy, particularly in the context of a physician shortage in France, which exacerbates the pharmacist's role. Recognizing these bleedings, which impair the quality of life for women, is an essential role of pharmacists and could be crucial in preventing the risk of discontinuing anticoagulant treatment. Methods We conducted an anonymous survey from December 2023 to January 2024 among pharmacists in France to explore their experiences with patients on anticoagulants who presented at pharmacies with questions about AUB. Results Of the 115 respondents, only 9 (7.8%) pharmacists had been approached by patients with questions about AUB while on anticoagulants. These pharmacists reported a majority of cases in women of reproductive age, the drug the most frequently cited was rivaroxaban. No significant demographic differences were observed between the pharmacists who had faced these questions and those who had not. Additionally, 99 (86.1%) pharmacists considered that they did not have enough skills to adequately advise female patients about abnormal uterine/genital bleeding under anticoagulant therapy. Conclusion Our study showed that community pharmacists are not the primary healthcare contact for patients with AUB under anticoagulant therapy. Despite this, the low frequency of pharmacist-patient interactions regarding AUB suggests potential under-diagnosis and under-communication of adverse effects that negatively impact the quality of life of women on anticoagulants.